Impact of feed restriction and housing hygiene conditions on specific and inflammatory immune response, the cecal bacterial community and the survival of young rabbits. (17th October 2016) - Combes, S.; Massip, K.; Martin, O.; Furbeyre, H.; Cauquil, L.; Pascal, G.; Bouchez, O.; Le Floc'h, N.; Zemb, O.; Oswald, I. P.; Gidenne, T.
Abstract : Limiting the post-weaning intake of the young rabbit is known to improve its resistance to digestive disorders, whereas a degradation of its housing hygiene is assumed to have a negative impact on its health. This study aims at providing insights into the mechanism of digestive health preservation regarding both host (growth and immune response) and its symbiotic digestive microbiota. A 2×2 factorial design from weaning (day 28) to day 64 was set up: ad libitum intake or restricted intake at 70% of ad libitum, and high v. low hygiene of housing ( n =105 per group). At day 36 and day 45, 15 animals/group were subcutaneously immunized with ovalbumin (OVA) to assess their specific immune response. Blood was sampled at 36, 45, 57 and 64 days of age to determine total and anti-OVA immunoglobulin type G (IgG) and haptoglobin levels. The cecal bacterial community was explored (18 per group) by 454 pyrosequencing of genes coding for the 16S ribosomal RNA, whereas cecal pH, NH3 and volatile fatty acid (VFA) concentrations were measured to characterize fermentative activity. A 30% reduction in feed intake reduced the growth by only 17% ( P <0.001), and improved the feed conversion ratio by 15% ( P <0.001), whereas the degradation of hygiene conditions slightly decreased the feed intake in ad libitum fed rabbits (−3.5%, P <0.02). As poor hygiene conditions did not affect weight gain, feed conversion was improved from day 42 ( P <0.05). Restricted feeding led to a lower mortality between day 28 and day 40 ( P =0.047), whereas degraded hygiene conditions decreased overall morbidity (7.8% v. 16.6%; P <0.01). Both a reduced intake and low hygiene conditions of housing affected microbiota composition and especially dominant genera belonging to the Ruminococcaceae family ( P <0.01). Moreover, low hygiene was associated with a higher Ruminococcaceae / Lachnospiraceae ratio (3.7 v. 2.4; P <0.05). Cecal total VFA and pH were increased (+19%; P <0.001) and decreased (−0.1 pH unit; P <0.05), respectively, in feed-restricted rabbits. Neither specific anti-OVA IgG nor haptoglobin was affected by treatments. Total IgG concentrations were the highest in animals raised in poor hygiene conditions after 8 days of restriction, but decreased after 19 days of restriction in high hygiene conditions (−2.15%; P <0.05). In conclusion, the degradation of hygiene conditions failed to induce a systematic specific and inflammatory response in rabbit, but reduced morbidity instead. Our results suggest that the microbiota composition would be a helpful source of biomarkers of digestive health.